Islam and Indonesian Nationalism; the Political Thought of Haji Agus Salim - Kahfi, Emi Haryanti (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
This article discusses aspects of socio-political religious thought Haji Agus Salim. Although the main concern in the effort to synthesize Salim understanding between Islam and nationalism, this article also highlights a variety of political views. He once tried to analyze different exploits Agus Salim in the world of practical politics, religious organizations, to government posts.DOI:Â 10.15408/sdi.v4i3.771